Implementation of business simulation games as learning tool: an example from University of Algarve - Kikot, Tatiana (2013)
Game-based learning environments in education are a valuable asset, as well as their potential benefits are unquestionable (Guillén-Nieto & Aleson-Carbonell, 2012). Yet, recent studies concerning academic achievement have reported contradictory or ambiguous findings. It is also interesting that empirical studies devoted to Management courses are not abundant and focus on: single unit courses (e.g., Edelheim & Ueda, 2007), units with low levels of interdisciplinarity (e.g., Pasin & Giroux, 2011), non-longitudinal studies (e.g., Sørensen, 2011) or games usability (e.g., Blažič et al., 2012). Therefore, the leading Author produced the following research query: can GBL (Cesim Global Challenge) be a useful and productive tool to support Management students for effective learning towards complex contexts while enhances engagement? A case study approach will be used (University of Algarve).